Morphological characteristics of flashing jet throughout superheated liquid release. (July 2020) - Zhu, Xueliang; Song, Zeyang; Pan, Xuhai; Mei, Yu; Wang, Xilin; Zhu, Yucheng; Jiang, Juncheng
Abstract: Many release problems involve two-phase releases of hazardous materials of superheated liquids with high energy into the atmosphere. Such accidents are accompanied by violent phase transition and form catastrophic flashing jets. In this work, experimental and theoretical analyses were conducted to investigate dynamic characteristics of flashing jet morphology and their dependence on pressure-decay dynamics under different storage pressures, superheats, and nozzle diameters. Flashing jet morphology and angle throughout two-phase releases were captured by a high-speed camera, and the corresponding source pressure in the superheated liquid tank was measured simultaneously. Results show that three typical phases, expansion, stabilization, and decay, are characterized throughout two-phase release based on the evolution of flashing jet morphology. The jet initially expands gradually due to the enhancement of phase transition intensity, and then keeps stable when the intensity reaches its maximum, and terminally decays rapidly due to the depletion of superheated liquid. Phase transition intensity at the nozzle exit is mainly controlled by the pressure-decay dynamics. Bubbles nucleation inception sites gradually move upstream of the nozzle during the pressure decay process increasing the phase transition intensity. The increase of storage pressure, superheat and nozzle diameter promotes the mechanical and thermodynamic effects on the jet breakup. The significant increase of mechanical and thermodynamic effects effectively accelerates droplets evaporation and further affects flashing jet morphology. Highlights: Experiments on flashing jet morphology under decayed pressure was conducted. Three characteristic phases throughout superheated liquid release were acquired. Dependence of flashing jet morphology on pressure-decay dynamics were obtained. Effects of storage pressure, superheat and nozzle diameter were investigated.